Primary Bilateral Arenal Lmphoma: A case report - Ali Shahriariahmadi; Nader Djangioskouie; Shabnam Salimi; Babak Izadi (International Journal of Hematology-Oncology and Stem Cell Research, 2005)
Primary adrenal lymphoma is extremely rare. We report a case with primary bilateral adrenal lym-phoma in a young male patient. He presented with abdominal pain and weight loss. Pathologic study revealed malignant lymphoma, diffuse large cell type (T- cell origin). Patient recieved combination chemotherapy and radiation therapy but 22 months after diagnosis died because of progression of dis¬ease